The effect of coaches’ ethical leadership behavior on athletes’ accountability and performance of Iraq player: Moderating role of psychological control - Emad Toma Radi; Louay Abdulsttar Salal; Shaimaa Jassim (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
Coaches play a crucial effect on player performance. The positive attitude and guidance of coaches improve the performance of restricted players. The national and international players in Iraq must contend with unethical conduct on the part of their coaches. This research aims to increase players' performance in Iraq by fostering a favorable interaction between coaches and athletes. This research attempted to investigate the impact of coaches' ethical leadership conduct on the accountability and performance of Iraqi athletes, with psychological control serving as a moderator. This study collected data using a Likert scale questionnaire, and the participants were Iraqi gamers who played various games. 400 replies are analyzed in this study, and the structural equation model is employed to analyze the data. This study concludes that psychological control moderates the relationship between coaches' ethical leadership conduct, athletes' accountability, and players' performance. This research's theoretical framework is an important contribution to the corpus of knowledge. The practical ramifications of this study are remarkable for enhancing the performance of athletes in Iraq. The study demonstrates that Iraqi athletes require ethical coaching to improve their performance.